Enunciados des/reterritorializados e a (des)legitimação do paradigma monolíngue - Santos, Alinee Silva dos (2017)
This dissertation seeks to identify the territorialities in which de/(re)territorialized statements published by the media transit. The purpose is analyzing how those statements, at the same time, delegitimize and reaffirm values of truth in relation to the monolingual paradigm. The research, a qualitative approach and documentary orientation (RAMALHO; RESENDE, 2011), sees the advertisements as media texts, therefore, formal research materials that we can apprehend meanings that manifest themselves according to the view of the researcher. In addition, those advertisements are a main corpus composed of nine statements, taken from the Facebook page of El Pancho, a translated Mexican food restaurant, which are understood as a file of de/(re)territorialized statements. The theoretical framework is divided into three parts: (1) the pillars of the monolingual paradigm and its effects (CANAGARAJAH, 2013; MIGNOLO, 2003), associated with the notions of native and non-native speaker (FIGUEREDO, 2011) and territory, the Nation-State, national language and stranger/foreigner (ALBUQUERQUE JR., 2012; CANAGARAJAH, 2013; ZOLIN-VESZ, 2015; BAUMAN, 2016, 2017); (2) research that have been conducted in the area of language studies (MIGNOLO, 2003) and applied linguistics (JACQUEMET, 2005, 2016; Cox-PETERSON, 2006; ASSISI-PETERSON, 2008; CANAGARAJAH, 2013) with the intention of discussing the monolingual paradigm; and (3) the contribution of the concept of de/(re)territorialized statement (ZOLIN-VESZ, 2016) in order to discuss the monolingual paradigm. The questions that guided the research were: 1) What are the territorialities which carried over the listed de/(re)territorialized statements in this research?, and 2) Which values of truth, in relation to the monolingual paradigm, are legitimate and which ones are not? The results of this research suggest that, although the monolingual paradigm has plastered the concept of language and confined it to specific territories, the setting of the contemporary world create opportunities to the uprising of de/(re)territorialized statements that unbalance the stability of values of truth tied to the monolingual orientation. However, at the same time that de/(re)territorialized statements destabilize those values, they seem to demonstrate that a “natural” equivalence between territory and language still remains in our conception of language. This can be perceived through the inclusion of the Spanish language in advertisements of a restaurant that offer a specific kind of food translated as Mexican.